Comprehensive characterization of phytochemicals and biological activities of the Italian ancient apple 'Mela Rosa dei Monti Sibillini'. (November 2020) - Nkuimi Wandjou, Joice Guileine; Lancioni, Laura; Barbalace, Maria Cristina; Hrelia, Silvana; Papa, Fabrizio; Sagratini, Gianni; Vittori, Sauro; Dall'Acqua, Stefano; Caprioli, Giovanni; Beghelli, Daniella; Angeloni, Cristina; Lupidi, Giulio; et al.
Graphical abstract: Highlights: The 'Mela Rosa dei Monti Sibillini' is an ancient apple cultivar of central Italy. Two sample preparation procedures were used for extracts. 20 phytochemicals were quantitatively determined by HPLC-DAD-MS. The fruit part influences the chemical composition of the final extract. The antioxidant and anti-inflammatory activities were measured. Abstract: This study was carried out to characterize extracts from nine samples of the apple 'Mela Rosa dei Monti Sibillini' (MR) and to assess the antioxidant and anti-inflammatory activities. The extracts were analysed by High Performance Liquid Chromatography coupled with photodiode array detector and mass spectrometry (HPLC-DAD-MS) for 20 phytochemicals. The extracts from the lyophilized material (ELM) were richer in polyphenolic compounds than the dried ones (EDM). The MR extracts contained noteworthy amounts of the investigated analytes compared to one sample of the commercial varieties Annurca, Golden Delicious and Granny Smith used as reference. Principal component analysis (PCA) revealed that the part of the fruit seems to have a significant influence on the chemical composition of the final extract; thus, the peel extracts exhibited higher levels of phenolic compounds, especially epicatechin, procyanidin B2 and phloridzin, and triterpenes than the pulp ones. In general, the lyophilized material showed higher antioxidant activity than the dried material. The strong antioxidant capacity of the MR has also been revealed by the DPPH, ABTS, FRAP and Folin-Ciocalteau assays. The ELM of MR significantly reduced reactive oxygen species in lipopolysaccharide (LPS)-activated mouse brain microglia cells (BV-2 cells). Real-time polymerase chain reaction (RT-PCR) analysis demonstrated that the EDM and ELM of MR were effective in reducing pro-inflammatory cytokines and enzymes in BV-2 and peripheral blood mononuclear cells (PBMC). These results contribute to the exploitation of this ancient variety as a source of nutraceuticals.